2018
DOI: 10.3892/or.2018.6484
|View full text |Cite
|
Sign up to set email alerts
|

DKC1 serves as a potential prognostic biomarker for human clear cell renal cell carcinoma and promotes its proliferation, migration and invasion via the NF‑κB pathway

Abstract: DKC1, an X‑linked gene encoding dyskerin at Xq28, is a crucial component of the telomerase complex and is indispensable for normal telomere function and the post‑-transcriptional modification of precursor rRNA. It has been revealed to exert diverse biological functions and prognostic values in numerous types of cancers. Our present study was aimed at examining DKC1 expression in normal renal tissues and clear cell renal cell carcinoma (ccRCC) samples and the prognostic value of DKC1 in ccRCC. We examined DKC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The current study confirms the significant association between the high expression of DKC1, at both protein and mRNA levels, and clinicopathological parameters characteristics of poor prognosis and with shorter survival; findings which are in-line with other studies. 15 , 44 , 45 Some studies have also confirmed that DKC1 overexpression is involved in tumorigenic processes and has prognostic value in numerous types of cancer. 19 , 21 , 46 The association between DKC1 mRNA and shorter survival was identified in both METABRIC and TCGA cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…The current study confirms the significant association between the high expression of DKC1, at both protein and mRNA levels, and clinicopathological parameters characteristics of poor prognosis and with shorter survival; findings which are in-line with other studies. 15 , 44 , 45 Some studies have also confirmed that DKC1 overexpression is involved in tumorigenic processes and has prognostic value in numerous types of cancer. 19 , 21 , 46 The association between DKC1 mRNA and shorter survival was identified in both METABRIC and TCGA cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…DKC1 is highly expressed in clear cell renal cell carcinoma. DKC1 knockout inhibits tumor proliferation, migration, and invasion by regulating the NF-κB/MMP-2 signaling pathway in vitro (Zhang M. et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al 21 suggested that loss of NOP10 may inhibit lung cancer cell growth, colony formation, migration, and invasion indicating that NOP10 has an oncogenic role in NSCLC. Zhang et al 22 suggested that the expression of DKC1 in clear cell renal cell carcinoma (ccRCC) was markedly higher than that in adjacent tissues, and knockdown of DKC1 inhibited ccRCC progression through the NF-κB/MMP-2 signaling pathway. Another study by Elsharawy et al 23 indicated that the overexpression of DKC1 contributes to the proliferation and progression of aggressive breast cancer.…”
Section: Introductionmentioning
confidence: 99%